2022
DOI: 10.3390/toxins14100694
|View full text |Cite
|
Sign up to set email alerts
|

Early Adverse Reactions to Snake Antivenom: Poison Center Data Analysis

Abstract: Antivenom is an essential treatment for snake envenomation; however, early adverse reactions (EARs) are major limitations to its use. We performed a retrospective cross-sectional study using Ramathibodi Poison Center data (January 2016 to December 2017) to clarify the incidence and severity of EARs following different F(ab’)2 antivenoms. Among 1006 envenomed patients, 684 (68%) received antivenom therapy with a total of 1157 doses, mostly green pit viper antivenom. The overall EAR incidence and rate were 22. 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The recommended dose of the Thai Red Cross is 5 vials of monovalent Malayan or Banded Krait antivenom or 5 vials of Polyvalent neurotoxic antivenom. Although the rate of early adverse reactions is high and can be life-threatening, these reactions are well controlled if appropriate monitoring is in place and adrenaline at hand [11].…”
Section: Significance For Clinical Management Of Neurotoxic Envenomin...mentioning
confidence: 99%
See 2 more Smart Citations
“…The recommended dose of the Thai Red Cross is 5 vials of monovalent Malayan or Banded Krait antivenom or 5 vials of Polyvalent neurotoxic antivenom. Although the rate of early adverse reactions is high and can be life-threatening, these reactions are well controlled if appropriate monitoring is in place and adrenaline at hand [11].…”
Section: Significance For Clinical Management Of Neurotoxic Envenomin...mentioning
confidence: 99%
“…A recent publication from Thailand showed that 154 out of 684 (22.5%) developed early adverse reactions (EARs) and 30 (4.4%) an anaphylactic shock. Under close monitoring during antivenom administration and appropriate treatment of EARs, no death was reported [ 11 ].…”
Section: Side Effects Of Horse-derived F(ab) 2 Ant...mentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, they found most of the sample presented with bleeding, in the proportion of (60,4%) and (59,1%). [10], [11], [13], [19] Based on the literature, Zinc Metalloproteinase contained in snake venom is responsible for a spontaneous bleeding incident after a venomous snake bite, also this component is said to have a role in inhibiting platelet aggregation, induced apoptosis, and hemorrhagic effect. Bleeding after a snake bite is also associated with Venom-Induced Consumption Coagulopathy (VICC)., which is marked by a low level of fibrinogen that causes coagulopathy.…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%
“…The escalating rates of snakebite-related mortality and amputations in low- and middle-income countries can be attributed to the inadequate availability of antivenoms, substandard healthcare services, variations in antivenom efficacy, and limited ability to mitigate local damage caused by venom variation intra- and interspecifically. Additionally, adverse reactions to antivenom further complicate this issue [ [12] , [13] , [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%